Prevalence and associated factors of sarcopenia in elderly subjects with amnestic mild cognitive impairment or Alzheimer disease. - Sugimoto, Taiki; Ono, Rei; Murata, Shunsuke; Saji, Naoki; Matsui, Yasumoto; Niida, Shunpei; Toba, Kenji; Sakurai, Takashi (Current Alzheimer Research, 2016)
Background: To date, very little is known about the nature of sarcopenia in subjects with cognitive impairment. The aims of this study were firstly to clarify the prevalence of sarcopenia at various stages of cognitive impairment, and secondly to examine factors related to sarcopenia in men and women with cognitive impairment. Method: The subjects were 418 outpatients (normal cognition; NC: 35, amnestic mild cognitive impairment; aMCI: 40, Alzheimer disease; AD: 343) who attended the Memory Clinic at the National Center for Geriatrics and Gerontology of Japan during the period from October 2010 to July 2014. Cognitive status, vitality, depressive mood, body mass index, hand grip strength, timed up and go test, skeletal muscle mass and serum levels of 25-hydroxyvitamin D, albumin and creatinine were assessed. Sarcopenia was defined as the presence of both poor muscle function (low physical performance or low muscle strength) and low muscle mass. We performed the univariate and multivariate logistic regression analyses to explore factors associated with sarcopenia. Results: The overall prevalence of sarcopenia was 21.1% (NC = 8.6%, aMCI = 12.5%, AD = 23.3%). In both sexes, factors associated with sarcopenia were age (P < .01), body mass index (P < .001) and vitality (P < .05). In women, serum level of 25-hydroxyvitamin D was associated with sarcopenia (P < .05). Conclusion: Low vitality could be a dementia-specific risk factor for sarcopenia. Prevention of sarcopenia in patients with cognitive impairment should be approached from physical and psychologic points of view.
Keywords: amnestic mild cognitive impairment